(untitled) (Belügyi Szemle, 2025)
Aim: This study examines the opportunities available to individual countries to act jointly and effectively against cross-border crime, with particular emphasis on the potential embedded in education. Methodology: In addition to the legislation, recommendations, and best practices related to CEPOL’s functioning, the study presents European Union law enforcement training based on the author’s personal experience. Findings: Beyond tracing the development and operation of CEPOL, the study provides insights into why a unified European law enforcement training system is important and necessary. Value: The paper is practice-oriented and seeks to offer a comprehensive overview of CEPOL’s role and history.